2009
DOI: 10.1111/j.1095-8312.2009.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal club cells and the innate immune system of minnows

Abstract: Thousands of fish species belonging to the Superorder Ostariophysi possess specialized club cells in their epidermis. Damage to the cells, as would occur during a predator attack, releases chemical substances that evoke antipredator responses in nearby shoalmates. These chemical substances have often been referred to as alarm substances and the cells that release them as alarm cells. Understanding the evolution of the cells in an alarm context has been difficult. The fish needs to be captured prior to the chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 24 publications
8
40
0
Order By: Relevance
“…It certainly needs clarification whether the above inconsistency is related to the fish skin condition, insufficient acclimatisation time, the influence of selective breeding, parasite specific host life cycle, or invasion intensity. These results are in accord with the hypothesis that club cells of common carp are a part of an integrated response to the parasitic damage of host epidermis (Smith 1992, Chivers et al 2007, Halbgewachs et al 2009). …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It certainly needs clarification whether the above inconsistency is related to the fish skin condition, insufficient acclimatisation time, the influence of selective breeding, parasite specific host life cycle, or invasion intensity. These results are in accord with the hypothesis that club cells of common carp are a part of an integrated response to the parasitic damage of host epidermis (Smith 1992, Chivers et al 2007, Halbgewachs et al 2009). …”
Section: Discussionsupporting
confidence: 90%
“…The cell-mediated innate mechanisms of epidermal tissues include specialized cells such as macrophages, granulocytes, natural killer cells, and also physical barriers such as mucous layers and skin epithelial tissue lines (Jones 2001, Aoki et al 2008. The epidermal club cells of many fishes in the superorder Ostariophysi have evolved primarily as part of the immune system (Chivers et al 2007, Halbgewachs et al 2009, Ferrari et al 2010 but their functional mechanisms, with non-specific and/or specific immunity, have not been explored in detail. The evolution of club cells of ostariophysan fish remains enigmatic and controversial as it has been historically linked to chemical alarm signalling (von Frisch 1941, Smith1992, James et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the median portion of this epithelium, the presence of club cells is similar to that observed in other species of teleosts, as they are round, with central nuclei and do not react with the routine staining techniques (Bart and Page, 1991;Berra et al, 1989;Flaxman, 1972;Halbgewachs et al, 2009;Koumans and Sire, 1995;McCormick and Larson, 2007;Stabell and Vegusdal, 2010;Strussmann et al, 1994;Zaccone et al, 2001).…”
Section: Discussionsupporting
confidence: 75%
“…In particular, mucous cells are known to be responsive to general irritative insults through hyperplasia and mucous discharge as an adaptive and protective reaction (Ferguson 2006). Halbgewachs et al (2009) found that the number of club cells in fathead minnows (Pimephales promelas) decreased significantly after cortisol injection, suggesting their role in the immune response. Fish taste buds consist of several cellular components and enable the animal to identify food by detecting distinct chemical substances at a short distance (Kasumyan 1997).…”
Section: Discussionmentioning
confidence: 98%